1971
DOI: 10.1126/science.174.4014.1131
|View full text |Cite
|
Sign up to set email alerts
|

Radiological Physics Characteristics of the Extracted Heavy Ion Beams of the Bevatron

Abstract: Studies of the depth-ionization properties and the biological effects of heavy ion beams produced at the bevatron have extended work previously done with less energetic beams from other sources. Results indicate that heavy ion beams are suitable for tumor therapy, studies relating to space biology, and fundamental radiobiology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0

Year Published

1977
1977
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(27 citation statements)
references
References 5 publications
1
26
0
Order By: Relevance
“…As compared with conventional photon beam treatment, ion beam radiotherapy takes advantage of the favorable depthdose distribution of ions (Bragg curve) expressed by the highest dose deposition deep in the tissue (1)(2)(3). On the basis of the advantageous physical properties, proton beam therapy is currently used in several centers in the United States, Europe, and Asia (4)(5)(6).…”
Section: Introductionmentioning
confidence: 99%
“…As compared with conventional photon beam treatment, ion beam radiotherapy takes advantage of the favorable depthdose distribution of ions (Bragg curve) expressed by the highest dose deposition deep in the tissue (1)(2)(3). On the basis of the advantageous physical properties, proton beam therapy is currently used in several centers in the United States, Europe, and Asia (4)(5)(6).…”
Section: Introductionmentioning
confidence: 99%
“…While intensity modulated radiation therapy (IMRT) and image guided radiation therapy (IGRT) using photons are two outstanding examples of such recent developments in radiation therapy [1], the most notable instance in the field of a vastly improved therapeutic gain would be that derived from charged particle radiation therapies with accelerated carbon ions or protons [1]. Accelerated carbon ions and protons have been very successfully used for treating solid cancers primarily due to their advantageous property of excellent physical dose-distribution and deposition around the Bragg peak [2,3]. Several recent clinical studies have reported that outcomes from charged particle beam radiation therapy yield equivalent or superior outcomes to surgical modalities in a number of cases such as prostate, lung, head and neck, bone and soft tissue tumors [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Clinical application of protons and carbon ions for human cancer treatment has been expanding and has achieved significantly improved clinical outcomes for a number of tumor types, including OSA in non-resectable tumors (8). Unlike conventional photon radiation, protons and carbon ions may be manipulated to release the majority of their energy only when they reach their target (7,9). This property is known as the Bragg peak.…”
Section: Introductionmentioning
confidence: 99%
“…This property is known as the Bragg peak. Particle radiation therapy offers the possibility of a significantly increased dose of ionizing radiation to the tumor with very little dose deposited in the normal tissue (7)(8)(9). Particle radiation therapy has the potential to be considered as an alternative modality for the treatment of canine and human OSA in the future.…”
Section: Introductionmentioning
confidence: 99%